HUBUNGAN TUGAS DAN BEBAN PEMBELAJARAN TERHADAP TINGKAT STRES MAHASISWA TAHUN PERTAMA FAKULTAS KEPERAWATAN SELAMA PEMBELAJARAN JARAK JAUH (PJJ) DI MASA PANDEMI - Nanik Saryati Hutabarat; Veny Elita; Wasisto Utomo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Distance Learning is the solution for carrying out teaching and learning activities during pandemics and causing first-year students to experience academic stress. This study aims to determine the factors that cause stress in first-year students of the Faculty of Nursing, Riau University, during distance learning in the COVID-19 pandemics. This study used a descriptive correlation research design using a cross-sectional approach. The research sample was 134 respondents who were taken based on inclusion criteria using the total sampling technique. The analysis used univariate analysis to see the frequency distributions and bivariate using the Chi-Square test. The instrument used is the questionnaire Depression Anxiety Stress Scale (DASS) and the Perceived Stress Scale (PSS) via google form consisting of 28 statements that have been tested for validity with r count 0.599-0.802 > r table (0.444) and r count 0.548-0.740 > r table (0.444). This study showed that the majority of students experienced moderate stress (52.2%). It is indicated that the factors related to student's academic stress are the task and learning load (p=0.00. The result of the research level of academic stress in first-year students of the Faculty of Nursing, Riau University is in the moderate category. The results of this study are expected to be used as a source of information in efforts to prevent student academic stress during the COVID-19 pandemic.Keywords: Academic Stress Levels, COVID-19 Pandemic, Distance Learning, Nursing Students